PARASTERNAL BLOCK: AN EXPERIENCE REPORT (CIPEEX, 2026)
Introduction: Parasternal block is a regional anesthesia technique used for analgesia in thoracic surgeries, providing comfort and reducing postoperative opioid use. Guided by ultrasound, the block targets the anterior cutaneous branches of the intercostal nerves in the fascial plane between the pectoralis major and external intercostal muscles. Objective: To report the experience of second-year medical students in a parasternal block procedure following a cardiac valve replacement surgery due to mitral stenosis. Method: This is an observational experience report carried out at the Hospital Evangélico Goiano, during a cardiac surgery for mitral valve replacement in a 41-year-old female patient. The observation encompassed the application of the Safe Surgery Protocol up to the performance of the bilateral ultrasound-guided parasternal block with 0.55% Ropivacaine and Dexmedetomidine. Results: The experience enabled the understanding of the technical principles of the block, the importance of ultrasound anatomical visualization, the role of multidisciplinary teamwork in facing challenges such as vascular access difficulties, and the application of the safety checklist. The technique showed benefits such as reduced opioid consumption and early ventilatory recovery. Conclusion: The activity integrated theory and practice, contributing to the technical and ethical training of the students. Direct exposure to regional anesthesia reinforced the value of humanization and safety in perioperative care.
Keywords: Anesthesia; Branch block; Intercostal nerves